Scoping irresponsible behaviour in hospitality and tourism: Widening the perspective of CSR - Volgger, Michael; Huang, S. (Emerald Group Publishing Limited, 2018)
Purpose: This paper aims to broaden the understanding of social responsibility in hospitality and tourism by positioning it in the wider context of responsibilities for deviant behaviour. The paper presents a critical literature review that scopes responsible and irresponsible behaviour of different stakeholders in hospitality and tourism and tackles some of the often-unquestioned assumptions of CSR, including who should be held accountable for ensuring responsibility (“the onus of responsibility”). Design/methodology/approach: The paper follows the methods and structure of a critical, concept-driven literature review. The literature review is inclusive in terms of its source material and covers different research traditions and study fields. Findings: The paper helps to overcome two unquestioned assumptions of CSR, i.e. that tourism responsibility is located best at the self-regulating business level and that responsible behaviour is preferred as a focus which oftentimes overshadows the issue of irresponsible behaviour. CSR is positioned as one approach amongst many to govern and tackle deviant tourism behaviour. Moreover, CSR’s blind spot on irresponsibility is removed. Originality/value: The paper is the first one to integrate the literature of CSR in hospitality and tourism with the literature on deviant tourism behaviour and on corporate social irresponsibility and can thereby cross-fertilise and broaden the three perspectives. The paper contributes to the literature by substantially widening the perspective of CSR in hospitality and tourism, thus opening new avenues of research.